2012
DOI: 10.1002/acr.21564
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for Progressive Multifocal Leukoencephalopathy among patients with selected rheumatic diseases

Abstract: We conducted a large, population-based study to describe the incidence and risk factors for progressive multifocal leukoencephalopathy (PML) among patients with rheumatoid arthritis (RA), psoriatic arthritis (PsA), psoriasis (PsO), juvenile idiopathic arthritis (JIA), inflammatory bowel disease (IBD), and ankylosing spondylitis (AS) using national inpatient and outpatient administrative data from the entire Center for Medicare and Medicaid Services (CMS) from 2000–2009. Suspected PML cases were identified usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 16 publications
2
25
0
2
Order By: Relevance
“…PML is a demyelinating disease preferentially affecting the white brain matter and is caused by the cytopathic replication of JCPyV in myelin sheath-producing oligodendrocytes. A Swedish and a US study estimated the incidence of PML in the general population as 0.3 per 100 000 person years (95% CI 0.1-0.6) compared to 1.0 (95% CI 0.3-2.5) for patients with rheumatoid arthritis (165)(166)(167). Similar data were reported for a US study estimating PML in systemic lupus erythematosus, rheumatoid arthritis, and other connective tissue disease as 4, 0.4, and 2 per 100 000 hospital discharges, respectively, whereas the PML incidence was 0.2 per 100 000 hospital discharges in the background population (167).…”
Section: Jcpyv Diseasementioning
confidence: 99%
“…PML is a demyelinating disease preferentially affecting the white brain matter and is caused by the cytopathic replication of JCPyV in myelin sheath-producing oligodendrocytes. A Swedish and a US study estimated the incidence of PML in the general population as 0.3 per 100 000 person years (95% CI 0.1-0.6) compared to 1.0 (95% CI 0.3-2.5) for patients with rheumatoid arthritis (165)(166)(167). Similar data were reported for a US study estimating PML in systemic lupus erythematosus, rheumatoid arthritis, and other connective tissue disease as 4, 0.4, and 2 per 100 000 hospital discharges, respectively, whereas the PML incidence was 0.2 per 100 000 hospital discharges in the background population (167).…”
Section: Jcpyv Diseasementioning
confidence: 99%
“…Another study in the USA used data from Medicare and Medicaid Services, and a PML incidence of 0.2 per 100,000 patients was found among 2,030,578 patients with ARDs. Of nine patients, who used bDMARDs prior to PML hospitalization, three (one receiving infliximab for inflammatory bowel disease, and the other two rituximab for RA) received them within 3 months [152]. One study found the estimated risk of PML in patients with RA receiving rituximab to be 1:25,000 users; unfortunately, this calculation was based on case reports and number of exposures, and not from a case-controlled study [153].…”
Section: Prevalence Of Pml In Ardsmentioning
confidence: 96%
“…Biologic therapies, including RTX, are also potentially associated with an increased risk of progressive multifocal leukoencephalopathy [51]. This is a rare, fatal, central nervous system demyelinating disease that results from reactivation of the JC virus, which usually occurs in immunosuppressed hosts.…”
Section: Retreatment and Safetymentioning
confidence: 99%